Rancang Bangun Aplikasi Klaim Garansi Produk Berbasis Web - Rachmanita, Novia; Oktarini Sari, Ani; - UBSI, Astrilyana; - STMIK Nusa Mandiri, Adelia Alvi Yana (IJNS - Indonesian Journal on Networking and Security, 2019)
Abstrak – Business competition nowadays is getting tighter, because more and more companies are emerging lately. therefore distributors or electronics stores compete to provide the best service for customer satisfaction. Cornerstone Electronic Store is a distributor or electronics store engaged in the sale of electronic devices. Especially electronics media players. Warranty System on distributors or stores Cornerstone Electronics currently uses Warranty claim system manually. This system requires customers to come to the store or distributor by bringing a memorandum of purchase & product to be fixed. The Customers must come back to the store or distributor if they want to know the progress of the product improvement process. The design of the application claim that this web is the best solution for this store / distributor. As Well as with a computerized system can be achieved an effective and efficient warranty claim activities in support of activities on this store or distributor. The design of this web-based warranty claims application using system software development method with waterfall method, and for web design using PHP scripting Langugage, HTML, CSS and for database design using MysQL. In writing this final project, the authors limit the scope of the problem to the web-based warranty claim application. With these problems the authors make a web-based warranty claim application to make it easier for customers to make warranty claims & can easily find out the repair status of the product that has been claimed by the customer without having to come to an electronic store / distributor. Kata kunci: Application design, Product warranty claims , Web-based warranty claims, E-Warranty Abstrak - Persaingan bisnis saat ini semakin ketat, karena semakin banyak perusahaan yang muncul belakangan ini. oleh karena itu distributor atau toko elektronik bersaing untuk memberikan layanan terbaik untuk kepuasan pelanggan. Toko Elektronik Cornerstone adalah distributor atau toko elektronik yang bergerak dalam penjualan perangkat elektronik. Terutama pemutar media elektronik. Sistem Garansi pada distributor atau toko Cornerstone Electronics saat ini menggunakan sistem klaim Garansi secara manual. Sistem ini mengharuskan pelanggan untuk datang ke toko atau distributor dengan membawa nota pembelian & produk untuk diperbaiki. Pelanggan harus kembali ke toko atau distributor jika mereka ingin mengetahui kemajuan proses peningkatan produk. Desain aplikasi mengklaim bahwa web ini adalah solusi terbaik untuk toko / distributor ini. Serta dengan sistem komputerisasi dapat dicapai kegiatan klaim garansi yang efektif dan efisien dalam mendukung kegiatan di toko atau distributor ini. Perancangan aplikasi klaim garansi berbasis web ini menggunakan metode pengembangan perangkat lunak sistem dengan metode waterfall, dan untuk desain web menggunakan PHP scripting Langugage, HTML, CSS dan untuk desain basis data menggunakan MysQL. Dalam penulisan tugas akhir ini, penulis membatasi ruang lingkup masalah pada aplikasi klaim garansi berbasis web. Dengan masalah-masalah ini penulis membuat aplikasi klaim garansi berbasis web untuk memudahkan pelanggan untuk membuat klaim garansi & dapat dengan mudah mengetahui status perbaikan produk yang telah diklaim oleh pelanggan tanpa harus datang ke toko elektronik / distributor. Kata kunci: Desain aplikasi, Klaim garansi produk, Klaim garansi berbasis web, E-Warranty